Pengaruh Service Quality terhadap Repurchase Intention melalui Customer Satisfaction: Perspektif Penumpang Lion Air - Nur Aminah; Dewi, Citra Kusuma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of air transportation in Indonesia is increasingly rapid, and low-cost airlines (low-cost carriers) dominate the market share of domestic airline passengers in Indonesia. Lion Air is one of the leading low-cost airlines (LCC), which has a high number of passengers. This research aims to test the influence of service quality on customer satisfaction, service quality on repurchase intention, and the relationship between service quality on repurchase intention which is mediated by customer satisfaction. The research methodology used is descriptive-quantitative causality. The data analysis technique uses structural equation modeling with partial least squares (SEM-PLS) with SMARTPLS 3 software. The results of hypothesis testing show that service quality (PV, RD, SI) has a statistically significant influence on customer satisfaction and also state that service quality (EC, SA) does not have a significant influence statistically on customer satisfaction. Service quality has a direct impact on the likelihood of customers making repeat purchases, just as customer satisfaction also influences the likelihood of repeat purchases. Customer satisfaction is influenced by service quality, which in turn influences repurchase intentions.